Assessment of poverty among the employees of the University of Gezira: Empirical analysis, 2006 - Babiker, Khalid; Elmulthum, Nagat; Ahmed, Muddathir (Gezira Journal of Agricultural Science; Vol 8 No 1 (2010), 2010)
This study aimed at estimating an income poverty line based on calorie requirements along with the different poverty indices, by applying the estimated poverty line to income distribution data for people working at the University of Gezira.  To estimate the poverty line, Annand and Nur (1988) methodology was followed using three selected consumption baskets to represent different consumption habits in Sudan. Applying the prices of 2006 on the consumption items of the selected baskets, the average cost of these baskets was obtained representing a minimum cash requirement for food consumption. Multiplying the above minimum cash requirement for food consumption by a conversion factor of 2, we obtained the poverty line for the year 2006. To estimate the poverty indices, the traditional measures of poverty such as the headcount, depth of poverty, severity of poverty, Gini Coefficient and Sen’s measure were applied. Results showed that the household income poverty line for the year 2006 was equal to SD 74202.48 (approximately equivalent to $371)  per month with a household size of 6.6. The head count index using expenditure and income approaches was equal to 48% and 54%, respectively. Moreover, results showed that the depth and severity of poverty using expenditure approach were equal to 17% and 8%, respectively, however, the depth and severity of poverty using income approach were equal to 24% and 13%, respectively. Regarding Sen's measure and Gini coefficient, results indicated that income was unequally distributed among the employees of the University of Gezira. In addition, results showed that the poverty indices using expenditure approach were below the poverty indices using income approach. This result may be attributed to the fact that people usually underestimate their income levels, hence, expenditure reflects the standard of living better than income.  تهدف هذه الدراسة إلى تقدير خط الفقر على أساس الاحتياجات من السعرات الحرارية وتقدير مختلف مؤشرات الفقر وذلك من خلال تطبيق خط الفقر المقدر على توزيع الدخل لبيانات العاملين في جامعة الجزيرة. لتقدير خط الفقر اتبعت الدراسة المنهجية التي استخدمها (1988) Annand and Nur وذلك باستخدام ثلاث سلات لتمثيل مختلف العادات الاستهلاكية في السودان. بتطبيق أسعار (2006) على سلات الغذاء التي تم اختيارها تحصلنا على التكلفة المتوسطة والتي تمثل الحد الأدنى للمتطلبات النقدية لاستهلاك الغذاء. تم تقدير خط الفقر بضرب الحد الأدنى للمتطلبات النقدية لاستهلاك الغذاء بمعامل التحويل 2 . بتطبيق خط الفقر على بيانات توزيع الدخل للعاملين بجامعة الجزيرة تحصلنا على تقديرات لمؤشرات الفقر التقليدية مثل مؤشر تعداد الرؤوس، مؤشر فجوة الفقر (عمق الفقر) ، مؤشر حدة الفقر ، معامل جيني ومؤشر سن . وضحت النتائج أن خط الفقر يساوي 74202.48 دينار شهرياً ويعادل (371$) في الشهر عام 2006م للأسرة التي متوسط عدد أفرادها يساوي 6.6 . أوضحت النتائج ان مؤشر تعداد الرؤوس بالنسبة للعاملين بجامعة الجزيرة يساوي 48% و 54% باستخدام منهج الإنفاق والدخل على التوالي وأن مؤشر عمق الفقر وحدة الفقر باستخدام منهج الدخل يساويان 17% و 8% على التوالي. في حالة استخدام منهج الإنفاق وضح أن عمق وحدة الفقر يساويان 24% و 13% على التوالي. باستخدام مؤشر سن ومعامل جيني وضح أن توزيع الدخل في صفوف العاملين بجامعة الجزيرة غير عادل. كذلك أوضحت النتائج أن مؤشرات الفقر باستخدام منهج الإنفاق أقل من مؤشرات الفقر باستخدام منهج الدخل ويمكن أن تعزى هذه النتيجة إلى أن الإنفاق يعكس مستوى المعيشة بصورة أفضل من الدخل.